A NEW APPROACH TO THE TREATMENT OF LARGE PARAVAGINAL HEMATOMAS - Сергей Владимирович Баринов; Татьяна Владимировна Кадцына; Юрий Игоревич Чуловский; Юлия Игоревна Тирская; Оксана Вячеславовна Лазарева; Евгения Сергеевна Надёжина; Ольга Альбертовна Гребенюк (The Publishing House Medicine and Enlightenment, 2022)
The aim of the research - to improve the results of treatment of patients with large paravaginal hematomas based on the developed modified method using the Zhukovsky vaginal catheter. Materials and methods. 15 puerperas with large paravaginal hematomas (more than 10 cm) were under observation. Surgical treatment included a pararectal incision in combination with the use of a Zhukovsky vaginal catheter. Results. Primiparas accounted for 53.3 %, multiparous 33.3 %, multiparous 13.3 %. Paravaginal hematomas in 33.3 % were combined with ruptures of the vagina, cervix. In the early postpartum period, paravaginal hematomas were found most often in 86.7 %. In 20 % of cases, hematomas were diagnosed without damage to the vaginal wall; in 66.7 % with damage to the vaginal wall. The total volume of blood loss during the use of a vaginal catheter was 850 (665; 925) ml. There were no significant changes in hemostasis and hemoglobin in the observed patients. Conclusion. The use of an integrated approach in the treatment of patients with large paravaginal hematomas can reduce blood loss, reduce the risk of postoperative complications, and reduce the duration of hospitalization.